Rehabilitation of degraded tropical forest ecosystems: workshop proceedings, 2-4 November 1999, Bogor, Indonesia - Kobayashi, S.; Turnbull, J.W.; Toma, T.; Mori, T.; Majid, N.M.N.A. (Center for International Forestry Research, 2001)
This conference proceedings contains 26 papers based on the activities of partner institutions that the Center for International Forestry Research (CIFOR) has facilitated. There are 4 sections: (i) evaluation of forest harvesting and fire impacts on forest ecosystems; (ii) development of methods to rehabilitate logged-over forests and degraded forest lands; (iii) development of silvicultural techniques on degraded forest lands; and (iv) network of the rehabilitation of degraded forest ecosystems.